METODE TARTIL DALAM MENINGKATKAN KEMAMPUAN MEMBACA JUZ AMMA PADA ANAK USIA 5-6 TAHUN DI PAUD MEKAR KARYA III KECAMATAN CIRACAP - Pipih Hapsoh; Indra Zultiar, Ibnu Huri (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This researcher aims to: (1) To find out how the tartil method is applied in improving the Juz Amma reading ability of children aged 5-6 years in PAUD Mekar Karya III, Ciracap District. (2) To find out the results of applying the tartil method in improving the ability to read Juz Amma in children aged 5-6 years at PAUD Mekar Karya III, Ciracap District. This type of research is classroom action research. The data sources in this research are parents and teachers. The subjects in this research were 15 children aged 5-6 years in PAUD Mekar Karya III, Ciracap District. The data collection techniques used in this research are: observation, interviews and documentation. The data analysis technique used is a subjective test, where the educator's imagination is realized through exhibitions, meetings and perceptions. The results of this research concluded that in the implementation process it was seen that 15 students in cycle I showed very good development (BSB). The learning pattern in cycle II has reached the benchmark for research success with a percentage of Developing According to Expectations (BSH) of 33% and Developing Very Well (BSB) of 40% to 73%, therefore the action ends in the implementation of cycle II.